Politik Sufisme: Studi Kasus Afiliasi KH. Musta’in Romly dalam Partai Golkar - M. Ubaidillah Hunaini (PUTIH: Jurnal Pengetahuan Tentang Ilmu dan Hikmah, 2022)
Every personal of a Sufi has a high sensitivity and concern for others. To be able to fight for the religion of God, sometimes a Sufi must enter into things of a worldly nature. Not because of aim or impulses that are not good and because of the attraction or even love for things that are oriented to world, but because of the existence of goals that are unwittingly positive. That's the way was when a Sufi was affiliated to politics. This article aims to uncover what motives and contributions were made from Dr. KH. Musta'in Romly as an Nusantara Sufi who had been involved in politics, and even entered one of the political parties. At that time, the case became a bit of a conflagration and gained some opposition from some quarters. The research of this article results that there are many contributions that Kiai Musta'in produced when he entered politics, especially when he joined the Golkar party. This can be shown from the aspects that return to general public, especially NU residents and aspects that return to the big family of Darul Ulum Islamic Boarding School and TQN Rejoso.